A rare case report of cervicofacial necrotizing fasciitis: The flesh-eating bacteria syndrome - Shrutika Ravindra Sonawane; Harshawardhan Babanrao Sawane; Lavanya H Pasalkar; Arunima Sarma (Wolters Kluwer Medknow Publications, 2022)
Cervicofacial necrotizing fasciitis is a fatal infection of the orofacial region that spreads rapidly through the subcutaneous tissues and fascia causing extensive necrosis and gas formation. Due to high morbidity and mortality rates, accurate diagnosis and immediate treatment are of utmost importance to avoid the devastating complications associated with it. This case report is of a 55-year-old male, reported with suppuration in the left aspect of the neck. Due to acute, aggressive, and rapidly progressive character of the infection, this report was written to create awareness about such a fatal infection and highlight the importance of accurate diagnosis and prompt treatment.